2016
DOI: 10.1308/rcsann.2016.0198
|View full text |Cite
|
Sign up to set email alerts
|

Routes of early enteral nutrition following oesophagectomy

Abstract: INTRODUCTION Oesophagectomy for cancer is a challenging procedure with a five-year overall survival rate of 15-20%. Early enteral nutrition following oesophagectomy is a crucial component of the postoperative recovery and carries a significant impact on the outcome. Different methods of enteral feeding were conducted in our unit. The aim of this study was to examine the efficacy and safety of nasojejunal tube (NJT), jejunostomy tube (JT) and pharyngostomy tube (PT) feeding after oesophagectomy. METHODS A retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…Parenteral nutrition has its own risks, such as central line sepsis, but has an advantage in that the decision to administer nutritional support may be postponed until the postoperative phase of recovery, when patients’ early postoperative courses can better indicate a need for such support. An alternative method of enteral access that is receiving more attention is nasojejunal tube placement at operation[ 13 , 14 ]. This modality is less invasive than jejunostomy tubes or central lines with fewer associated complications, but is more aimed towards supplemental nutrition while the patient is in-house as opposed to long-term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parenteral nutrition has its own risks, such as central line sepsis, but has an advantage in that the decision to administer nutritional support may be postponed until the postoperative phase of recovery, when patients’ early postoperative courses can better indicate a need for such support. An alternative method of enteral access that is receiving more attention is nasojejunal tube placement at operation[ 13 , 14 ]. This modality is less invasive than jejunostomy tubes or central lines with fewer associated complications, but is more aimed towards supplemental nutrition while the patient is in-house as opposed to long-term.…”
Section: Discussionmentioning
confidence: 99%
“…Options for nutritional support following upper gastrointestinal resection include needle catheter jejunostomy, Stamm or Witzel jejunostomy, or nasojejunal feeding tube placement[ 9 - 14 ]. In some centers, feeding jejunostomy (FJT) is routinely performed following esophagectomy or total gastrectomy, with more selective utilization with subtotal gastrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis of 90 patients who underwent esophagectomy demonstrated that early enteral nutrition can be administered using three different routes (nasojejunal tube, jejunostomy tube, and pharyngostomy tube) with similar results regarding tube-related complications, length of stay, and 30-day morbidity [92]. Another study of esophageal cancer patients with dysphagia examined the effects of jejunostomy feeding on weight loss and treatment outcomes.…”
Section: Type Of Feedingmentioning
confidence: 99%
“…While up to 38% of feeding jejunostomy tubes are associated with minor complications (eg, entry site infection, entry site leakage, gastrointestinal complaints), 20‐35% of nasojejunal tubes dislocate during the course of hospitalization . To date, no clear evidence for superiority of either feeding route exists and, hence, both techniques are used . For patients that have resumed oral intake but cannot yet meet their caloric and protein demands, enteral feeding can be provided as a supplement to the patients oral diet .…”
Section: Perioperative Periodmentioning
confidence: 99%
“…[66][67][68] To date, no clear evidence for superiority of either feeding route exists and, hence, both techniques are used. 66,69 For patients that have resumed oral intake but cannot yet meet their caloric and protein demands, enteral feeding can be provided as a supplement to the patients oral diet. 14,65,70,71 The most recent ESPEN "Clinical Nutrition in Surgery" guidelines recommend early initiation of enteral tube feeding in case patients cannot eat for at least 5 days or when oral intake is expected to be inadequate (ie, <50%) for more than 7 days.…”
Section: Feeding Routesmentioning
confidence: 99%